Complaint : grievance among friends - Ronell, Avital (University of Illinois Press, 2018)
"Everyone has a complaint, but nobody likes a complainer. Rather than making things better a complaint can just make things worse. Often its only relief is the harmless and temporary release of steam. But it can also pose as criticism in one of several seemingly respectable forms. In Complaint, Avital Ronell looks at how complaints and complainers have been treated in literature and philosophy, in feedback loops that pay little attention to injustice and suffering. Beginning with Hamlet, and with open awareness of her own experiences, Ronell proceeds to show how complaining is aggravated, distracted, stifled, and transformed. She looks at exemplary complaints made by Friedrich Nietzsche, Hannah Arendt, and Barbara Johnson. She examines the complaint riven history of deconstruction. Renowned for her courage in taking on painful subjects with candor and wit, Ronell dares to listen to the haunting complaints of the dead"--